Financial Capital, Internal Risk Resilience, Entrepreneurship, and Financial Capability of Households in Chongqing, China - Liu, Li; Eamurai, Poramet (วารสารนวัตกรรมการศึกษาและการวิจัย, 2026)
Finance serves as the cornerstone of the modern economy and a fundamental driver of rural revitalization in China. This study employs an explanatory sequential mixed-methods design to examine how financial resource availability (FRA) influences poverty reduction (PR) among rural households in Chongqing, while testing the mediating roles of farmer entrepreneurship (FE) and risk resilience (RRRH), and the moderating role of financial capability (FC). Quantitative data were collected from 504 households and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), followed by 14 qualitative interviews analyzed with NVivo. Results show that FRA significantly reduces rural poverty and strongly promotes both FE and RRRH. RRRH mediates the FRA–PR relationship, while FE does not. FC significantly moderates the effect of FRA on PR. Qualitative findings highlight structural and cultural barriers that limit entrepreneurship, while underscoring resilience and financial literacy as decisive for poverty alleviation. These results contribute to theory by clarifying the mechanisms linking FRA, adaptive capacities, and household outcomes, and inform policy by emphasizing inclusive finance, risk protection, and financial education.